2018
DOI: 10.1016/j.bbadis.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Klotho protects the heart from hyperglycemia-induced injury by inactivating ROS and NF-κB-mediated inflammation both in vitro and in vivo

Abstract: Cardiac inflammation and oxidative stress play a key role in the pathogenesis of diabetic cardiomyopathy (DCM). The anti-aging protein Klotho has been found to protect cells from inflammation and oxidative stress. The current study aimed to explore the cardioprotective effects of Klotho on DCM and the underlying mechanisms. H9c2 cells and neonatal cardiomyocytes were incubated with 33mM glucose in the presence or absence of Klotho. Klotho pretreatment effectively inhibited high glucose-induced inflammation, RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 64 publications
5
94
0
Order By: Relevance
“…It may be due to protection from death caused by oxidative stress and induction of oxidative stress resistance by Klotho. Importantly, several studies have previously proved the antioxidative, antiapoptotic and antifibrotic activity of Klotho 9,17,43,45 . These findings confirm the beneficial influence of Klotho on cell metabolism and survival observed in our research.…”
Section: Discussionsupporting
confidence: 92%
“…It may be due to protection from death caused by oxidative stress and induction of oxidative stress resistance by Klotho. Importantly, several studies have previously proved the antioxidative, antiapoptotic and antifibrotic activity of Klotho 9,17,43,45 . These findings confirm the beneficial influence of Klotho on cell metabolism and survival observed in our research.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our previous study found that systemic administration of α-klotho had a pro-lipolytic effect on liver and the white adipose tissue (Rao et al, 2019). Furthermore, α-klotho has been demonstrated to have a protective effect on the heart and kidneys (Guo et al, 2018;Lim et al, 2018). Generally, there are two forms of αklotho, a full-length (130 kDa) and a shorter form (65 kDa) (Xu and Sun, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the expression of α-klotho in some organs is low or absent, α-klotho is still important to maintain the normal function of these organs. For example, a study (Guo et al, 2018) demonstrated that exogenous α-klotho protected the heart form hyperglycemia-induced injury, even though it is well recognized that α-klotho is not expressed in the heart. Sahu et al (2018) found that α-klotho was upregulated in the young injured muscle, which was important for muscle regeneration and that muscle regeneration could be promoted by the supplement of α-klotho (aa34-981, R&D).…”
Section: Introductionmentioning
confidence: 99%
“…28 It acts as a cardioprotective factor in maintenance of cardiovascular homeostasis by suppressing vascular endothelial dysfunction, delaying vascular calcification, correcting sinoatrial node function and cardiac rhythm, and protecting heart from cardiac hypertrophy, senescence, and damage. [29][30][31] As demonstrated previously in humans, higher plasma klotho levels are independently related to a lower likelihood of cardiovascular disease events, 32 and in contrast, reduced systemic klotho levels are related to cardiovascular damage. 33 The expression of Klotho gene is decreased during aging or in response to other pathogens, which appears to play a critical role in the pathogenesis of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 93%